Seconds - Conolly, Jez; Westwood, Emma (Constellations (Leighton Buzzard, England), 2021)
Seconds (1966) is John Frankenheimer's criminally overlooked parable of paranoia - part SF, part body horror, part thriller cum black comedy, and arguably the bleakest mainstream Hollywood film ever made. This Constellation illuminates the film's many attributes, and contends that Seconds is both emblematic of the time in which it was made and perpetually relevant to new audiences.